HUNGARY IN IVAN FRANKO'S CREATIVITY AND SCIENTYFIC HERITAGE - Погребенник, В. (Київський національний університет імені Тараса Шевченка, 2022)
The article investigates the Ivan Franko's literature, historical-literature and historical works, dedicated to the Hungary. Its themes/motives is the main subject in text of short novel "The clean race", which are investigated in such aspects, as ideas, symbolic details and other. The author of article interprets too historical and literary senses and messages of I. Franko's scientific Hungarian studies, dedicated to the old time and actual new events, personage & problems in Austrian-Hungarian monarchy of the middle and end of XIX-th century. Ivan Franko's reasoning about old literature, folklore, historic events of the XIX-th century, as it proved in article, is still marked by deeply special knowledges, accurate definitions and symbolic assessments, interesting literary parallels, exspressed with meaning of the case with critical remarks. And its analyzed specifics of Hungary reception and using of his ideas of harmonisation of the international relations between Hungary and Ukraine. With good reason, in this article is emphasized I. Franko's skills as an observer and ethnopsychologist, a master of political senses, and finally as writer-democrat and scientist-polihistor, who promoted humanism, patriotism and high idealism, Ukrainian and Hungarian struggle for freedom.

Досліджуються угорські теми/мотиви літературної та наукової спадщини Івана Франка. Зокрема, охарактеризовано коло ідей, символічні деталі тощо оповідання "Чиста раса". Автор дослідження схарактеризував історичні і літературні сенси наукової унґаристики І. Франка, присвяченої давнім часам, та актуальним новим подіям і проблемам Австро-Угорської монархії середини-кінця ХІХ століття. Проаналізовано специфіку сприйняття і застосування Франкових ідей гармонізації міжнародних стосунків Угорщини і України.
УГОРЩИНА В ЛІТЕРАТУРНІЙ І НАУКОВІЙ СПАДЩИНІ ІВАНА ФРАНКА
Keywords: hungaristics; dialogue; literature image; discussion; history; political aspects; humanism; унґаристика; діалог; літературний імідж; дискусія; історія; політичні аспекти; гуманізм